A Guide to Good Occlusal Practice - Davies, Stephen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book considers occlusion within the different disciplines of clinical dentistry, taking into account the challenges specific to each, in order to develop guidelines of good occlusal practice (GGOP). The GGOP for each discipline has benefited from an authoritative contribution of a recognised specialist in that field. Readers will find full description of what constitutes good occlusal practice in, for example, simple and advanced restorative dentistry, removable prosthodontics, the restoration of the worn dentition and implantology. It is clearly explained why and how the GGOP differ in the various branches of dentistry, the key point being that it is the support for the occlusal surfaces that determines GGOP. One of the foundations of this work is that an occlusion can only be judged by the tissue reactions to it: there is no such thing as an intrinsically bad occlusion or malocclusion. Today it remains the case that many dentists feel that occlusion represents an important gap in their knowledge; indeed, some qualify with little more than the belief that (3z(Bocclusion is important(3y(B. Their vulnerability in this area of clinical practice is confirmed when early cases fail to go as well as hoped. In providing comprehensive guidance on good occlusal practice in different contexts, this book will be of value for a wide range of dental practitioners.s
Introduction -- What is Occlusion? -- Examination and Recording of the Occlusion -- Good Occlusal Practice in Simple Restorative Dentistry -- Good Occlusal Practice in Advanced Restorative Dentistry -- Good Occlusal Practice in Removable Prosthodontics -- Orthodontics and Occlusion -- Occlusal Considerations in Periodontology -- Good Occlusal Practice in Children$1 (Bs Dentistry -- Management of Tooth Surface Loss -- Good Occlusal Practice in Provision of Implanted Supported Prosthesis -- Bruxism.s
Keywords: Dentistry; Dentistry; Dental Occlusion